Mahathir's leadership communication for social change on Indian community in Malaysia: Indian Hindu spiritual values - S Maartandan, Suppiah (2019)
This research focuses on Mahathir’s leadership communication in creating social changes among Indians in Malaysia. Various studies were conducted on leadership communication but researches which touches on the leadership communication between a leader of a majority community (Malay) and his/her followers from the minority group (Indian) from the cultural perspective are limited. Therefore, this study investigates the leadership communication of Mahathir from the Indian perspective. The researcher interviewed Indians in Malaysia including leaders and commoners based on purposive sampling method. A total of 23 informants have been recruited as the study informants. Data were collected through interviewing, notetaking and audio recording. Descriptive accounts of the Indians’ responses towards Mahathir’s leadership communication for social changes from the Indian perspective were explored and presented using the transformational leadership theory. Based on the thematic analysis, five themes were emerged to answer the aims of the study; Indians leadership communication conception, Mahathir’s leadership communication, the influence of Indian culture towards Mahathir’s leadership communication, leadership communication for social change, responses to Mahathir’s leadership communication and the expectation of Indians towards leadership communication. Based on the findings of this study, a leadership communication model from the Indian perspective is developed which could be used as a reference in managing the Indians who are the minority community. This study provides an insight of leadership communication towards bringing social change, particularly focusing on the relationship of a leader and his followers from the minority community.